2017
DOI: 10.1098/rstb.2016.0033
|View full text |Cite
|
Sign up to set email alerts
|

The eco-evolutionary impacts of domestication and agricultural practices on wild species

Abstract: One contribution of 18 to a theme issue 'Human influences on evolution, and the ecological and societal consequences'. Agriculture is a dominant evolutionary force that drives the evolution of both domesticated and wild species. However, the various mechanisms of agriculture-induced evolution and their socio-ecological consequences are not often synthetically discussed. Here, we explore how agricultural practices and evolutionary changes in domesticated species cause evolution in wild species. We do so by exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 78 publications
0
63
0
2
Order By: Relevance
“…human-induced context reference type of manuscript key insight(s) pollution [23] review/empirical strong selection imposed by human-released chemical pollution can be mitigated by physiological adaptations such as enzymatic metabolic adaptations that could be costly in non-polluted conditions eutrophication [24] review/empirical eutrophication often leads to homogenization of both phenotype and genotype and to a loss of ecological specialization, which can have cascading effects at the community and ecosystem levels urbanization [25] review the type of urban disturbance can have different effects on adaptive traits of organisms in urban environments, which can affect ecosystem processes and thus eco-evolutionary dynamics urbanization [26] empirical consideration of both changes in community responses and evolutionary responses is important in understanding community trait changes resulting from urbanization, and trait change depends on the spatial scale at which urbanization is considered habitat fragmentation [27] review anthropogenic fragmentation generates selection at multiple scales; dispersal and associated traits are likely to adapt and evolve interactively; and these adaptations might not be enough for 'rescue' at the meta-population level habitat fragmentation (and urbanization) [28] empirical fragmentation predicted trait variation better than did urbanization, and reproductive and dispersal traits were altered as a result of adaptation to urban environments climate change [29] review/empirical the role of life-history plasticity and evolution in response to shifts in competition could help us to understand how climate change induced competition might affect local communities and biodiversity domestication/agriculture [30] review agriculture and domestication can drive evolution in wild species that can have large socioeconomic ramifications on ecosystem services. An understanding of these processes can help inform how to mitigate the impacts domestication/agriculture [31] empirical a comprehensive, phylogenetically controlled meta-analysis found that domestication influences the evolution of herbivore resistance, though the magnitude is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…human-induced context reference type of manuscript key insight(s) pollution [23] review/empirical strong selection imposed by human-released chemical pollution can be mitigated by physiological adaptations such as enzymatic metabolic adaptations that could be costly in non-polluted conditions eutrophication [24] review/empirical eutrophication often leads to homogenization of both phenotype and genotype and to a loss of ecological specialization, which can have cascading effects at the community and ecosystem levels urbanization [25] review the type of urban disturbance can have different effects on adaptive traits of organisms in urban environments, which can affect ecosystem processes and thus eco-evolutionary dynamics urbanization [26] empirical consideration of both changes in community responses and evolutionary responses is important in understanding community trait changes resulting from urbanization, and trait change depends on the spatial scale at which urbanization is considered habitat fragmentation [27] review anthropogenic fragmentation generates selection at multiple scales; dispersal and associated traits are likely to adapt and evolve interactively; and these adaptations might not be enough for 'rescue' at the meta-population level habitat fragmentation (and urbanization) [28] empirical fragmentation predicted trait variation better than did urbanization, and reproductive and dispersal traits were altered as a result of adaptation to urban environments climate change [29] review/empirical the role of life-history plasticity and evolution in response to shifts in competition could help us to understand how climate change induced competition might affect local communities and biodiversity domestication/agriculture [30] review agriculture and domestication can drive evolution in wild species that can have large socioeconomic ramifications on ecosystem services. An understanding of these processes can help inform how to mitigate the impacts domestication/agriculture [31] empirical a comprehensive, phylogenetically controlled meta-analysis found that domestication influences the evolution of herbivore resistance, though the magnitude is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Crop domestication and the concurrent global expansion of agriculture have dramatically altered ecosystems and have diverse evolutionary consequences [1]. One of these consequences is that interactions between plants and their insect herbivores can be significantly altered in agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Crops often suffer intense pressure from herbivores [2], and a commonly invoked hypothesis explaining high damage levels is that crop evolution under domestication has altered plant traits in a way that has decreased resistance to herbivores [3][4][5]. However, it can be difficult to disentangle the relative importance of domestication per se versus agricultural practices in shaping plant-herbivore interactions [1]. One approach to isolating the effects of domestication is to compare crops and wild relatives, and such comparisons have often shown that crops are less resistant to herbivores than their wild counterparts (reviewed in [6,7]).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, despite limited study, it is clear that crop domestication has had large impacts on herbivorous insect communities and on natural enemies of herbivores, such as parasitoids [117]. Evolution of wild species in response to agricultural practices can both directly and indirectly impact the provision of multiple ecosystem services, such as rapid evolution in pests, pathogens, and weeds causing stark declines in crop production [118].…”
Section: The Eco-evolutionary Impacts Of Domestication and Agriculturmentioning
confidence: 99%